2015
DOI: 10.1098/rstb.2015.0053
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily conserved mechanisms for the selection and maintenance of behavioural activity

Abstract: Survival and reproduction entail the selection of adaptive behavioural repertoires. This selection manifests as phylogenetically acquired activities that depend on evolved nervous system circuitries. Lorenz and Tinbergen already postulated that heritable behaviours and their reliable performance are specified by genetically determined programs. Here we compare the functional anatomy of the insect central complex and vertebrate basal ganglia to illustrate their role in mediating selection and maintenance of ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 109 publications
(202 reference statements)
1
70
0
Order By: Relevance
“…Finally, to gain insights into the behavioral impact of integrated supernumerary R neurons, we analyzed the motor behavior of lineage‐expanded flies. Ellipsoid body R neurons have been implicated in goal‐directed behavior, higher motor control, spatial orientation learning and memory, as well as in attention, arousal, and decision‐making, suggesting that R neurons are involved in the assessment of sensory information for adaptive behavior (Strausfeld & Hirth, ; Fiore et al , ). Indeed, previous studies showed that R neuron dysfunction affects sensory‐motor transformation and higher motor control (Fiore et al , ; preprint: Kottler et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to gain insights into the behavioral impact of integrated supernumerary R neurons, we analyzed the motor behavior of lineage‐expanded flies. Ellipsoid body R neurons have been implicated in goal‐directed behavior, higher motor control, spatial orientation learning and memory, as well as in attention, arousal, and decision‐making, suggesting that R neurons are involved in the assessment of sensory information for adaptive behavior (Strausfeld & Hirth, ; Fiore et al , ). Indeed, previous studies showed that R neuron dysfunction affects sensory‐motor transformation and higher motor control (Fiore et al , ; preprint: Kottler et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Simplified circuit maps for four nonmammalian model organisms where sensorimotor transformations are experimentally well studied. [100][101][102][103][104][105][106][107] Here, a combination of seeded sensorimotor loops and inhibition as well as compartmentalization enable the fly to integrate multiple senses in the CX and respond accordingly. [1,6,97] Inhibitory neurons are key in integrating information from the hair cells and photoreceptors to drive movement via cilia and tentacles.…”
Section: Independent Of the Evolutionary Age Of The Organism Inhibitmentioning
confidence: 99%
“…While it is possible that our selection of Gal4 lines was unintentionally biased against output neurons, or that our technique otherwise missed a number of output pathways, the picture of the central complex that emerges is of a densely recurrent sensorimotor hub with relatively low dimensional output (much as proposed by some models e.g. Stone et al 2017;Fiore et al 2015;Strauss and Berg 2010). The implications of this bottleneck for motor control remains a challenge for future studies to resolve.…”
Section: Central Complex Motifsmentioning
confidence: 99%